Strategy and environment as determinants of performance: Evidence from the Japanese machine tool industry - Kotha, Suresh; Nair, Anil (Strategic Management Journal, 1995)
Abstract This study examines the roles played by the environment and realized strategies on firm‐level performance in the Japanese machine tool industry. We examine the effect of environment and strategy on performance using longitudinal data on a sample of 25 Japanese machine tool firms over the period 1979‐92. Our results indicate that both firm strategies and the environment play significant roles in influencing profitability and growth. More specifically, whereas both strategy and environmental variables are significantly related to firm profitability, only environmental variables are associated with firm growth. Additionally, in contrast to U.S. based studies, we find that capital expenditures and technological change are not negatively associated with profitability. Rather technological change has a positive impact on firm growth. We discuss the implications of these results for strategic management and provide suggestions for future research.